Museum der Avantgarde - Die Sammlung Sonnabend New York. - Bonito Oliva, Achille; Celant, Germano; Froment, Jean-Louis; Joachimides, Christos M.; Ludwig, Peter; Panza, Giuseppe; Pincus-Witten, Robert; Rosenbaum, Allen; Szeemann, Harald; de Wilde, Edy; Hamburger Bahnhof - Museum für Gegenwart Berlin (Berlin : Electa Editrice Milano Hamburger Bahnhof - Museum für Gegenwart Berlin, 1988)
Acconci, Vito ; Anselmo, Giovanni ; Arman ; Baldessari, John ; Baselitz, Georg ; Becher, Bernd & Hilla ; Bickerton, Ashley ; Bochner, Mel ; Boltanski, Christian ; Bömmels, Peter ; Broodthaers, Marcel ; Calzolari, Pierpaolo ; Christo ; Dine, Jim ; Dokoupil, Jiri Georg ; Dunham, Carroll ; Fischli & Weiss ; Riverhead (New York) ; Gilbert & George ; Halley, Peter ; Höckelmann, Antonius ; Immendorff, Jörg ; Johns, Jasper ; Judd, Donald ; Kiefer, Anselm ; Koons, Jeff ; Kounellis, Jannis ; Lemieux, Annette ; LeWitt, Sol ; Lichtenstein, Roy ; Manzoni, Piero ; McCracken, John ; Merz, Mario ; Morris, Robert ; Nauman, Bruce ; Oehlen, Albert ; Oldenburg, Claes ; Paolini, Giulio ; Penck, A.R. ; Pistoletto, Michelangelo ; Poirier, Anne & Patrick ; Rauschenberg, Robert ; Rosenquist, James ; Sarkis ; Schifano, Mario ; Serra, Richard ; Sonnier, Keith ; Spoerri, Daniel ; Steinbach, Haim ; Twombly, Cy ; Le Va, Barry ; Vaisman, Meyer ; Warhol, Andy ; Wegman, William ; Wesselmann, Tom ; Winters, Terry ; Yarber, Robert ; Zorio, Gilberto
Duits
Museum der Avantgarde : Die Sammlung Sonnabend New York, Hamburger Bahnhof - Museum für Gegenwart Berlin, 7. Dezember 1988 - 26. Februar 1989
boek